Quality of life of mothers of children with congenital syndrome affected by zika virus - de Araújo Costa, Paulo Rogério Lobão; Arruda Aragão, Francisca Bruna; do Nascimento Serra, Jacira; Andrade, Marcelo Sousa; Reis, Andréa Dias [UNESP]; do Desterro Soares Brandão Nascimento, Maria (My University, 2020)
Objective: To investigate how mothers of children with congenital syndrome (microcephaly) associated with Zika virus perceive their quality of life. Methods: This is a qualitative study carried out in two stages: at the Maternal and Child University Hospital and at Casa de Apoio Ninar through semi-structured interviews with mothers of children with congenital syndrome associated with Zika virus. Ten women comprised the sample. Results: In line with the critical discourse analysis, four categories emerged based on Fairclough’s 2008 assumptions: Quality of Life and Health — quality of life perception associated with the broad meaning of the term health; Quality of Life and Health Care Systems — characterized by care instability and fragmentation; Quality of Life and Free Time — lack of free time for activities of daily living and leisure; Quality of Life and Future Perspectives — lack of future perspective, considering that most participants had to stop working and studying to take care of their children. Conclusions: Mothers of children with congenital syndrome associated with Zika virus are devoted to their children’s care. Their lack of prospects was considered a consequence of the lack of time for activities of daily living and leisure.
Qualidade de vida de mÃes de crianÇas com sÍndrome congÊnita afetadas pelo zika vÍrus
Keywords: Microcephaly; Quality of life; Zika virus